The geography of the world economy : - Knox, Paul L. (Arnold, 1998)
The Geography of the World Economy provides an in-depth and stimulating introduction to the theory and practice of economic geography. Giving emphasis to the 'globalisation' of the world economy and its interactions with both developed and developing countries, this textbook offers a consideration of local, regional and global economic development over the long historical term.